Effect of time dependent viscosity and radiation efficacy on a non-Newtonian fluid flow. Issue 2 (February 2019) - Hussain, Azad; Akbar, Sobia; Sarwar, Lubna; Nadeem, Sohail; Iqbal, Zaffar
Abstract: In the present article we have studied the radiation effects on the flow of a viscoelastic fluid flow past a spongy plate by considering the viscosity as variable. In order to explore the variable viscosity effects, law of conservation of mass, momentum and energy are flourished. The shooting method is adapted to accomplish the numerical solution of governing equations. The effects of the involved emerging parameters such as Reynolds' model viscosity numbers, Vogel's model viscosity numbers and Prandtl numbers on velocity and temperature profiles are discussed with the help of graphs. The associated physical properties of the flow i.e. the skin friction coefficient and Nusselt numbers are presented graphically for different parameters. The tables for effects of distinct parameters on temperature profile at the wall for Reynolds' model and Vogel's model are given. Impact of various parameters involved on Nusselt number and skin friction are also presented in tables.